Relevansi Convenientes ex Universo dalam Mewujudkan Keadilan Pendidikan Melalui Beasiswa Subsidi Silang di Yayasan Bina Wirawan - Martalia Odi; Theresia Noiman Derung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the application of the principle of Convenientes ex Universo in the cross-subsidy scholarship program organized by the Bina Wirawan Foundation. This study is based on the understanding that the Catholic Church, through the encyclical Convenientes ex Universo, places great emphasis on the importance of social justice, including in the field of education. The research method used is descriptive qualitative, with data collection through interviews. The research findings indicate that the cross-subsidy scholarship program at the Bina Wirawan Foundation successfully embodies the social justice values taught by the church. This program not only provides financial support but also creates an inclusive learning environment and fosters a spirit of solidarity among the students. However, this research also identifies several challenges faced, namely limited funding and the lack of participation from students coming from affluent families. The implication of this research is the importance of collaboration between various parties to ensure the sustainability and success of the cross-subsidy scholarship program in achieving educational justice.